Onesnaženost zunanjega zraka kot kontinuiran javnozdravstveni izziv - Carli, Tanja (Javno zdravje, 2021)
Ambient air pollution is a complex mixture of chemicals in gasseous and aeorosol form that can poses harmful effects on all components of the environment, including groundwater, soil, and air, hence directly and indirectly affect living organisms (people, animals, vegetation) and materials (possession). The International Agency for Research on Cancer (IARC) has classified ambient air pollution and PM particles as carcinogenic to humans (Group 1). From the view of particle size, it is likely that the greatest harm in susceptible individuals is caused due to exposure to high PM2,5 concentrations. In Slovenia, most epidemiological research has been oriented towards connection between the exposure to ambient air pollution and respiratory diseases. Little is known about the link between ambient air quality perception and objective measurements (environmental monitoring) of ambient air quality in the area, while the association between health inequalities and exposure to ambient air pollution remains unexplored.
Keywords: ambient air pollution; delci PM; onesnaženost zunanjega zraka; ozone; PM particles; prizemni ozon